Lucky : how Joe Biden barely won the presidency - Allen, Jonathan, (Jonathan J. M.); Parnes, Amie (Crown, 2021)
Presents the inside story of the historic 2020 presidential election and the string of chance events that resulted in Joe Biden's victory.